2018
DOI: 10.3389/fphar.2018.00941
|View full text |Cite
|
Sign up to set email alerts
|

Estrone-3-Sulfate Stimulates the Proliferation of T47D Breast Cancer Cells Stably Transfected With the Sodium-Dependent Organic Anion Transporter SOAT (SLC10A6)

Abstract: Estrogens play a pivotal role in the development and proliferation of hormone-dependent breast cancer. Apart from free estrogens, which can directly activate the estrogen receptor (ER) of tumor cells, sulfo-conjugated steroids, which maintain high plasma concentrations even after menopause, first have to be imported into tumor cells by carrier-mediated uptake and then can be cleaved by the steroid sulfatase to finally activate ERs and cell proliferation. In the present study, expression of the sodium-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…It has been described that the expression of the ER promotes the proliferation of the luminal cells lines MCF-7 and T47D. 108,109 This could explain why these cells have the higher expression of the cell cycle-related genes. Also, luminal cells have a smaller population of stem cells and a greater population of differentiated cells that are in constant proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that the expression of the ER promotes the proliferation of the luminal cells lines MCF-7 and T47D. 108,109 This could explain why these cells have the higher expression of the cell cycle-related genes. Also, luminal cells have a smaller population of stem cells and a greater population of differentiated cells that are in constant proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a transport function for sulfated steroids would not make sense physiologically for ASBT, because relevant levels of sulfated steroid hormones are not present in the lumen of the ileum. SOAT is more widespread in its expression and was detected in germ cells of the testis, skin, placenta, mammary gland and some other hormone-dependent tissues (Geyer et al, 2007;Fietz et al, 2013;Grosser et al, 2013;Karakus et al, 2018). By SOAT-mediated uptake of sulfated steroid hormones from the blood and subsequent cleavage by the steroid sulfatase (so-called intracrine steroid synthesis) seems to contribute to the steroid regulation of many hormone-dependent tissues (Geyer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…SOAT is expressed in breast cancer and here mediates the uptake of pro-proliferative sulfated estrogen precursors. Inhibition of SOAT had anti-proliferative effects in breast cancer cells in vitro, and so was proposed as potential novel anti-cancer drug target (Karakus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…SOAT1 is ubiquitously expressed in tissues and cells, while SOAT2 is predominantly expressed in the liver and intestines [23]. Reports indicated that SOAT1 is constitutively expressed and likely functions to maintain the intracellular balance of free and esterified cholesterol, whereas SOAT2 is associated with intestinal cholesterol absorption and hepatocyte-specific functions such as lipoprotein particle assembly and the production of bile, and SOAT1 is responsible for the formation of foam cell in macrophages [24, 25]. Previous studies also reported that SOAT1 was involved in the formation of atherosclerotic plaques, and was involved in regulating inflammation.…”
Section: Discussionmentioning
confidence: 99%